Social Security in Belgium : Distributive Outcomes - Alain Jousten; Mathieu Lefèbvre; Sergio Perelman; Pierre Pestieau (Institute for the Study of Labor (IZA), 2005)
The paper analyzes the link between old-age income programs and economic outcomes in Belgium. We use a simulation methodology to construct an average pension generosity variable. Our regression analysis explores the link with distributional outcomes in income, consumption and more subjective indicators. Results document the weak link between average generosity and distributional outcomes across a heterogeneous population.
Keywords: I32; H55; H31; I31; 330; pensions; inequality; social security; elderly; Gesetzliche Rentenversicherung; Einkommensverteilung; Alte Menschen; Schätzung; Belgien